IDNLearn.com offers a reliable platform for finding accurate and timely answers. Discover the reliable solutions you need with help from our comprehensive and accurate Q&A platform.
Sagot :
Certainly! Let's expand the expression [tex]\((x - 2)^8\)[/tex] step by step.
To expand [tex]\((x - 2)^8\)[/tex], we use the binomial theorem. The binomial theorem states that:
[tex]\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^k \][/tex]
In this case, [tex]\(a = x\)[/tex], [tex]\(b = -2\)[/tex], and [tex]\(n = 8\)[/tex]. So, we substitute these values into the binomial theorem:
[tex]\[ (x - 2)^8 = \sum_{k=0}^{8} \binom{8}{k} x^{8-k} (-2)^k \][/tex]
Now, let's compute each term in the sum:
1. For [tex]\(k = 0\)[/tex]:
[tex]\[ \binom{8}{0} x^{8-0} (-2)^0 = 1 \cdot x^8 \cdot 1 = x^8 \][/tex]
2. For [tex]\(k = 1\)[/tex]:
[tex]\[ \binom{8}{1} x^{8-1} (-2)^1 = 8 \cdot x^7 \cdot (-2) = -16x^7 \][/tex]
3. For [tex]\(k = 2\)[/tex]:
[tex]\[ \binom{8}{2} x^{8-2} (-2)^2 = 28 \cdot x^6 \cdot 4 = 112x^6 \][/tex]
4. For [tex]\(k = 3\)[/tex]:
[tex]\[ \binom{8}{3} x^{8-3} (-2)^3 = 56 \cdot x^5 \cdot (-8) = -448x^5 \][/tex]
5. For [tex]\(k = 4\)[/tex]:
[tex]\[ \binom{8}{4} x^{8-4} (-2)^4 = 70 \cdot x^4 \cdot 16 = 1120x^4 \][/tex]
6. For [tex]\(k = 5\)[/tex]:
[tex]\[ \binom{8}{5} x^{8-5} (-2)^5 = 56 \cdot x^3 \cdot (-32) = -1792x^3 \][/tex]
7. For [tex]\(k = 6\)[/tex]:
[tex]\[ \binom{8}{6} x^{8-6} (-2)^6 = 28 \cdot x^2 \cdot 64 = 1792x^2 \][/tex]
8. For [tex]\(k = 7\)[/tex]:
[tex]\[ \binom{8}{7} x^{8-7} (-2)^7 = 8 \cdot x \cdot (-128) = -1024x \][/tex]
9. For [tex]\(k = 8\)[/tex]:
[tex]\[ \binom{8}{8} x^{8-8} (-2)^8 = 1 \cdot 1 \cdot 256 = 256 \][/tex]
Adding all these terms together, we get:
[tex]\[ x^8 - 16x^7 + 112x^6 - 448x^5 + 1120x^4 - 1792x^3 + 1792x^2 - 1024x + 256 \][/tex]
So, the expanded form of [tex]\((x - 2)^8\)[/tex] is:
[tex]\[ x^8 - 16x^7 + 112x^6 - 448x^5 + 1120x^4 - 1792x^3 + 1792x^2 - 1024x + 256 \][/tex]
To expand [tex]\((x - 2)^8\)[/tex], we use the binomial theorem. The binomial theorem states that:
[tex]\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^k \][/tex]
In this case, [tex]\(a = x\)[/tex], [tex]\(b = -2\)[/tex], and [tex]\(n = 8\)[/tex]. So, we substitute these values into the binomial theorem:
[tex]\[ (x - 2)^8 = \sum_{k=0}^{8} \binom{8}{k} x^{8-k} (-2)^k \][/tex]
Now, let's compute each term in the sum:
1. For [tex]\(k = 0\)[/tex]:
[tex]\[ \binom{8}{0} x^{8-0} (-2)^0 = 1 \cdot x^8 \cdot 1 = x^8 \][/tex]
2. For [tex]\(k = 1\)[/tex]:
[tex]\[ \binom{8}{1} x^{8-1} (-2)^1 = 8 \cdot x^7 \cdot (-2) = -16x^7 \][/tex]
3. For [tex]\(k = 2\)[/tex]:
[tex]\[ \binom{8}{2} x^{8-2} (-2)^2 = 28 \cdot x^6 \cdot 4 = 112x^6 \][/tex]
4. For [tex]\(k = 3\)[/tex]:
[tex]\[ \binom{8}{3} x^{8-3} (-2)^3 = 56 \cdot x^5 \cdot (-8) = -448x^5 \][/tex]
5. For [tex]\(k = 4\)[/tex]:
[tex]\[ \binom{8}{4} x^{8-4} (-2)^4 = 70 \cdot x^4 \cdot 16 = 1120x^4 \][/tex]
6. For [tex]\(k = 5\)[/tex]:
[tex]\[ \binom{8}{5} x^{8-5} (-2)^5 = 56 \cdot x^3 \cdot (-32) = -1792x^3 \][/tex]
7. For [tex]\(k = 6\)[/tex]:
[tex]\[ \binom{8}{6} x^{8-6} (-2)^6 = 28 \cdot x^2 \cdot 64 = 1792x^2 \][/tex]
8. For [tex]\(k = 7\)[/tex]:
[tex]\[ \binom{8}{7} x^{8-7} (-2)^7 = 8 \cdot x \cdot (-128) = -1024x \][/tex]
9. For [tex]\(k = 8\)[/tex]:
[tex]\[ \binom{8}{8} x^{8-8} (-2)^8 = 1 \cdot 1 \cdot 256 = 256 \][/tex]
Adding all these terms together, we get:
[tex]\[ x^8 - 16x^7 + 112x^6 - 448x^5 + 1120x^4 - 1792x^3 + 1792x^2 - 1024x + 256 \][/tex]
So, the expanded form of [tex]\((x - 2)^8\)[/tex] is:
[tex]\[ x^8 - 16x^7 + 112x^6 - 448x^5 + 1120x^4 - 1792x^3 + 1792x^2 - 1024x + 256 \][/tex]
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Discover the answers you need at IDNLearn.com. Thanks for visiting, and come back soon for more valuable insights.